Use of Dalk in the Gynecological Diseases: Perspectives of Persian Medicine - Somayyeh Khalilzadeh; Malihe Tabarrai (Tehran University of Medical Sciences, 2019)
Women's diseases are types of the common problems that patients are seeking for treatment that imposes a lot of economic burdens on health systems. Many Persian medicine reference books mentioned various practical methods for the adjunctive treatment of the gynecological problems. In the Persian medicine resources, "Dalk" therapeutic method is the most appropriate word for massage. Many clinical studies have been conducted on applied massage in women's diseases which confirms the effects of "Dalk"in this regard. The purpose of this study is to investigate "Dalk"'s applications on women's diseases.